Book review: non-Invasive ventilation made simple - Jacinto, Tiago (2015)
Non-invasive ventilation (NIV) is well established and increasingly used in routine clinical practice, either in the management of acute respiratory failure, where it has resulted in improved survival and reduced number of complications or in weaning from invasive ventilation in intensive care or high-dependency units. However, some concepts and techniques of NIV may be difficult to grasp for students or for unexperienced healthcare professionals.